Seasonal dissolved copper speciation in the Strait of Georgia, British Columbia, Canada - Waugh, Lori-jon C.; Flores Ruiz, Iselle; Kuang, Cheng; Guo, Jian; Cullen, Jay T.; Maldonado, Maria T. (Frontiers in Marine Science, 2022)
The Strait of Georgia (SoG) is a semi-enclosed, urban basin with seasonally dependent estuarine water circulation, dominantly influenced by Northeast Pacific waters and the Fraser River. To establish a baseline and understand the fate and potential toxicity of Cu in the SoG, we determined seasonal and spatial depth profiles of dissolved Cu (dCu) speciation, leading to estimates of the free hydrated copper (Cu2+) concentrations, as a proxy for Cu toxicity. The concentration of dCu was largely controlled by conservative mixing of the ocean and freshwater endmembers in the SoG. In all samples, ligand concentrations exceeded dCu, by a ratio greater than 1.5, resulting in the complexation of 99.98% of the dCu by strong binding organic ligands. The concentrations of Cu2+ were less than 10-13.2 M, significantly lower than the well-established Cu toxicity threshold (10-12 M Cu2+) for microorganisms. Our results indicate that ambient Cu-binding ligands effectively buffer Cu2+ concentrations within the Strait of Georgia, posing no threat to marine life. In almost 90% of the samples, the ligands were best classified as a single ligand class, with a logK_(CuL,〖Cu〗^(2+))^cond between 12.5 and 14.1. The concentrations of these single class ligands were greatest in warm, low salinity, nutrient depleted waters, suggesting that either terrestrially sourced ligands dominate dCu speciation in the SoG, or freshwater sources in the SoG establish the conditions that promote the production of Cu binding ligands in its surface waters. The remaining 10% of the samples were from the euphotic zone, where we detected a stronger ligand class, L1, of logK_(CuL_1,〖Cu〗^(2+))^cond between 13.5 and 14.3, and a weaker ligand class, L2, of logK_(CuL_2,〖Cu〗^(2+))^cond between 11.5 and 12.3. In these surface samples, logK_(CuL_1,〖Cu〗^(2+))^cond and logK_(CuL_2,〖Cu〗^(2+))^cond were positively correlated with temperature, while L2 concentrations were positively correlated with chromophoric dissolved organic matter of terrestrial origin. This study is the first to perform hierarchal clustering of a trace metal speciation dataset and enabled the distinction of 6 clusters across season, depth, and region of the SoG, highlighting the influence of freshwater and open ocean ligand sources, conservative mixing dynamics, and particulate Cu concentrations on dCu speciation within estuarine basins.